Practice of Cancer Prevention Strategies among Staff of Federal Universities in North Central Zone, Nigeria - Akorede, Seun Nurudeen (Journal of Health Education, 2019)
Background: The high rate of death as a result of cancer in the world is worrisome, the trend as revealed in many literatures including World Health Organization, shows that cancer accounts for 12.5% of all deaths in the world. This study was conducted to assess practice of cancer prevention strategies among staff of Federal universities in North Central Zone, Nigeria.Methods: To achieve this purpose, ex-post facto research design was used. A total of 756 staff from seven federal universities in north central zone Nigeria with a population of twenty-five thousand three hundred and sixty-one 25,361 were selected through multi-stage sampling procedures of simple random, stratified, proportionate and accidental. The instrument used for the study was pilot tested with the use of Cronbach Alpha 0.859 was obtained respectively. Out of the 756 copies of questionnaire distributed, 752 were valid for analyses. Inferential statistics of one sample t-test, was used to test the data collected.Results: The results revealed that the staff of federal universities in north central zone Nigeria are poor in practice of cancer prevention strategies with P-value of 0.11 at 0.05 level of significance.Conclusions: Based on the results, the following conclusion was drawn; Cancer prevention strategies practice is poor among staff in Federal Universities of North-central Zone, Nigeria. Based on the conclusion, it was recommended that concerned Government and non-Governmental agencies and Ministry of Health should double efforts in ensuring that Federal University staff are provided adequate intervention programmes and Health Education on improved practice of cancer prevention strategies.